Detection of Sentinel Lymph Nodes During Breast Cancer Surgery: A Literature Overview - Šepetys, Gratas; Gudavičienė, Daiva; Jakutis, Nerijus (Lietuvos chirurgija, 2023)
Introduction. Detecting metastases is an important part of successful breast cancer treatment. Usually, the tumor tissue first spreads to the sentinel lymph nodes. Removal of the latter during surgery and histological examination allows to assess the patient’s disease stage, prognosis and treatment. The literature provides more than one approach or a combination of them, allowing us to accurately identify the breast’s sentinel lymph nodes and avoid removing all axillary lymph nodes. Purpose. To review the methods of intraoperative detection of breast sentinel lymph nodes presented in the literature. Research material and methods. Publications were searched using the specialized information search system Google Scholar. Keywords used in the search: breast sentinel lymph nodes, intraoperative detection. After evaluating the exclusion criteria, the review was based on 25 scientific publications. Results. 4 individual measures and 2 combinations of them can be used to detect sentinel breast lymph nodes during surgery. The materials used can be injected in 6 different ways. Conclusions. The combination of technetium-99m radiocolloid and methylene blue can be evaluated as the best method for intraoperative detection of sentinel lymph nodes in breast cancer patients. On the other hand, due to radiation and operating costs, more attention is being paid to the use of indocyanine green, superparamagnetic iron oxide, methylene blue dye, and the detection of metastases without surgery. Superficial methods of injecting the substance should be combined with deep ones due to the possibility of detecting extra-axillary sentinel lymph nodes of the breast. Ultimately, all decisions must be made on a case-by-case basis.
Keywords: Breast cancer; sentinel lymph nodes; intraoperative detection